Rule consequentialist perspectives on suicide - Nayır, Beşir Özgül. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Suicide has always been a philosophically interesting topic since the ancient times. It is questioned within different branches of philosophy, and moral philosophy is one of them. The moral question of suicide concerns with its moral permissibility as an act; therefore, it can be formulated as the following: Is it morally permissible to commit suicide? There are several ways to answer this question, but I believe most of the current answers are not sufficient. For this reason, I think it would be useful to use an alternative moral theory, what is called ‘Rule Consequentialism’. Despite it has roots in the history of philosophy, Rule Consequentialism has become a relatively popular idea only in the second half of the twentieth century. It is a critical approach to the well-known Act Consequentialism claiming that actual consequences of particular actions cannot be reliable sources to determine moral rightness or wrongness of an action. One should appeal to the universal moral rule defined by the Rule Consequentialism to determine if a course of action is morally right or wrong. In this study, I will present an interpretation of Rule Consequentialism. This will be a version of it with a special focus on the problem of suicide. After that, the Rule Consequentialist answer to the problem of suicide will be presented. This version of Rule Consequentialism suggests that committing suicide is morally permissible.
Keywords: Suicide.